Influence of Military Training and Standardized Nutrition in Military Unit on Soldiers' Nutritional Status and Physical Fitness. Issue 10 (October 2016) - Tomczak, Andrzej; Bertrandt, Jerzy; Kłos, Anna; Kłos, Krzysztof
Abstract : Abstract: Tomczak, A, Bertrandt, J, Kłos, A, and Kłos, K. Influence of military training and standardized nutrition in military unit on soldiers' nutritional status and physical fitness. J Strength Cond Res 30(10): 2774–2780, 2016—Despite suspension of conscription in Polish Army, trainings of soldiers are still carried out. It is expected that they will be effective and will contribute to obtaining optimum level of psychophysical efficiency that enables fulfillment of military tasks. Total of 60 soldiers took part in the study. During the 9-month military service, soldiers had 200 hours of physical training and basic military training (shooting, drill, anti-chemical training, topography, general tactics, and military equipment operation). The training lasted 8 hours everyday. To assess fitness level, 4 trials were done: long jump, pull-ups, sit-ups, and 1, 000 m run. Evaluation of food was based on the analysis of full board menus using the "Tables of composition and nutritional value of food products." Energy value was assessed, and content of basic nutrients was calculated. Assessment of nutritional status was based on anthropometric measurements, such as body height, body mass, and thickness of 4 selected skinfolds. Body height and body mass were the basis for the body mass index calculation. Soldiers serving in the mechanized infantry unit, after completing the training, got better results only in 1, 000 m run (from 250.3 to 233.61 seconds). During the research, an average energy value of a daily food ration planned for consumption was 4, 504 kcal. This value consisted of 13.2% of energy from protein, 31.9% of energy from fat, and 54.9% from carbohydrates. In the course of military service, percentage of subjects indicating overweight increased from 10.2 to 25.4%.